Miniaturization: The Clue to Clinical Application of the Artificial Placenta - Schoberer, Mark; Arens, Jutta; Erben, Aileen; Ophelders, Daan; Jellema, Reint K.; Kramer, Boris W.; Bruse, Jan L.; Brouwer, Petra; Schmitz-Rode, Thomas; Steinseifer, Ulrich; Orlikowsky, Thorsten (Artificial organs, 2014)
The artificial placenta as a fascinating treatment alternative for neonatal lung failure has been the subject of clinical research for over 50 years. Pumpless systems have been in use since 1986. However, inappropriate dimensioning of commercially available oxygenators has wasted some of the theoretical advantages of this concept. Disproportional shunt fractions can cause congestive heart failure. Blood priming of large oxygenators and circuits dilutes fetal hemoglobin (as the superior oxygen carrier), is potentially infectious, and causes inflammatory reactions. Flow demands of large extracorporeal circuits require cannula sizes that are not appropriate for use in preterm infants. NeonatOx, a tailored low‐volume oxygenator for this purpose, has proven the feasibility of this principle before. We now report the advances in biological performance of a refined version of this specialized oxygenator.